Selected dental anomalies in Ramadi population (Clinical and radiographic survey) (Mustansiria Dental Journal, 2018)
The form, size, shade and time of eruption of teeth in humans show very wide variation among different population and some times within the same population. Anomalies like Dilaceration, Taurodontism and recently Talon cusp were a subject for a large number of studies, Studies related to such anomalies in our community are very little and for this reason, this current research is carried out to provide a quick view on the prevalence of these anomalies in our community. The sample of this research composed of 1908 teeth from them the prevalence of the selected dental anomalies were recorded. The results showed that the prevalence of these anomalies where found to be 7.52 % in the maxillary teeth and 7.35% in the mandibular teeth and these anomalies were more frequent in molars and lateral incisors than other teeth.